Response: Demand Avoidance Phenomena: a manifold issue? Intolerance of uncertainty and anxiety as explanatory frameworks for extreme demand avoidance in children and adolescents – a response to Woods (2020). Issue 2 (17th March 2020) - Grahame, Victoria; Stuart, Lisa; Honey, Emma; Freeston, Mark
Abstract : This paper is in response to the commentary written by Richard Woods in which he attempts to provide support for his Monotropism autism theory and the research indicating that Demand Avoidance Phenomena may not be developmentally persistent (Woods, 2019). We acknowledge the continuing controversy around the proposed construct of PDA and the clinical dilemma faced by professionals, within the United Kingdom, following increased demand from families seeking assessment and support. We appreciate that research on this topic is scarce and understanding of PDA behaviours remains limited and that methodological improvements are required. However, it is important to remember that anxiety, which often has an onset in middle childhood and adolescence, is a major risk factor for mental health difficulties. Therefore, treatments targeting underlying and potentially modifiable mechanisms rather than anxiety symptoms may be more likely to be effective. Abstract : Read the commentary at doi: 10.1111/camh.12368 and full article at doi: 10.1111/camh.12336